2017
DOI: 10.1038/s41598-017-06502-7
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation of MEG3 Functions as a Potential Plasma-Based Biomarker for Cervical Cancer

Abstract: Methylation alterations of specific genes have recently been identified as diagnostic biomarkers for human cancers. Although MEG3 has been proved to be a tumor suppressor in cervical cancer according to our previous study, the diagnostic value of MEG3 methylation in plasma is still unknown. Therefore, the aim of this study is to identify a novel epigenetic biomarker for cervical cancer. In the current study, the level of MEG3 methylation was evaluated using methylation-specific polymerase chain reaction. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 22 publications
1
46
0
Order By: Relevance
“…36 Though little research describes aberrant methylation of MEG3, hypermethylation has been implicated as a potential biomarker in cervical cancer. 37 When estimating time-to-regression at a single follow-up visit, increased methylation at the Kv DMR also decreased the probability of regression relative to women who had lower levels of methylation. The Kv DMR is maternally methylated, comprised of the imprint control region IC2 located at Chr11p15.5, which regulates at least 11 imprinted genes.…”
Section: Discussionmentioning
confidence: 99%
“…36 Though little research describes aberrant methylation of MEG3, hypermethylation has been implicated as a potential biomarker in cervical cancer. 37 When estimating time-to-regression at a single follow-up visit, increased methylation at the Kv DMR also decreased the probability of regression relative to women who had lower levels of methylation. The Kv DMR is maternally methylated, comprised of the imprint control region IC2 located at Chr11p15.5, which regulates at least 11 imprinted genes.…”
Section: Discussionmentioning
confidence: 99%
“…Among these key lncRNA, several studies have reported that lncRNA MEG3 played crucial roles in the development of various cancers, such as: non-small cell lung cancer, cervical cancer, colorectal cancer, esophageal cancer. [39][40][41][42][43] The lncRNA MEG3 had effects to suppress cervical cancer by regulation of PI3K/AKT/Bcl-2/Bax/P21 and PI3K/AKT/ MMP-2/9 signaling pathways. However, only two studies demonstrated that lncRNA ADAMTS9-AS2 was associated with development of gliomas, 44 and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of 15 included studies had selected circulating HPV DNA as a detected gene target. Other gene targets had higher sensitivity but lower specificity, including SIM1 methylation [26], MEG3 methylation [28], Bmi-1 [29], miR-21 [30], and hsa-miR-92a [31].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies [10,24] increased the risk of bias owing to a lack of patient selection. Four studies [25][26][27][28] did not mention the use of a blinding method or reference standard, which may have resulted in an unknown risk of bias in the meta-analysis.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation